2017
DOI: 10.1177/0003489417694912
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cough Aerodynamics in Healthy Adults

Abstract: Cough aerodynamics can be readily measured objectively in the outpatient setting. Expiratory rise time, peak flow, and peak pressure are important aspects of each cough epoch. Normative data provided herein can be used for future studies of patients with laryngotracheal disorders, and these cough parameters may prove to be simple, accessible, and repeatable outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
(29 reference statements)
1
21
0
3
Order By: Relevance
“…The value of CPF was significantly lower in women than men in all age groups. Our finding consist with a previous reports that value of CPF was lower in women than in men 7,8,28) . Men demonstrated greater height and body weight than women.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The value of CPF was significantly lower in women than men in all age groups. Our finding consist with a previous reports that value of CPF was lower in women than in men 7,8,28) . Men demonstrated greater height and body weight than women.…”
Section: Discussionsupporting
confidence: 93%
“…One study showed that FVC, FEV1.0, and MIP in the 70-79year group were significantly lower than those in the 50-59year group in men, and that FVC, FEV1.0, MIP, and MEP in the 70-79-year group were significantly lower than those in the 50-59-year group in women 27 ) . Additionally, the value of CPF in the older group (50-80 years) was lower than in the younger group (20-49 years) 28 ) . Taken these other results and our own results into account, the tendency for a decline in CPF with ageing seems to be similar to that for other respiratory functions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Another study reported aPCF unassisted cut-off point of 2.77 L/s (166 L/min) predicted cough effectiveness [28]. Age adjusted PCF values have been published for children from the age of 4-18 years old [29] along with normal values for adults [30]. After the age of 12 years, PCF appears to be within the adult range, albeit at the lower limit [29].…”
Section: Peak Cough Flow (Pcf)mentioning
confidence: 99%
“…49 Laryngeal closure and opening connects to cough peak flow (CPF), the highest measured airflow spike during cough, appearing immediately after opening of the glottis during the cough cycle. 50,51 Duration of the cough compression phase has been suggested to primarily manipulate the pace of cough (fast/slow), whereas CPF affects the power of cough (strong/weak). 52 The threshold for clinically effective secretion removal has been proposed at CPF of 160-180 l/min.…”
Section: Cough Is Not a Cough Without A Functioning Larynxmentioning
confidence: 99%